Upaya Pencegahan Stunting Melalui Program Penyuluhan Kesehatan bagi Remaja untuk Mengatasi Anemia dengan Pemberian Buku Saku - Dini Fitri Damayanti; Dianna Dianna; Rakhmawati Rakhmawati (Compromise Journal Community Proffesional Service Journal, 2025)
Stunting does not occur in a short time, but is a long and repeated process of malnutrition starting from the womb. Efforts to prevent stunting can be done starting from adolescence. The health status of adolescents determines the quality of life as adults, especially adolescent girls. The most common health problem in adolescent girls is nutritional problems, namely anemia. Adolescent girls who suffer from anemia are at risk of becoming women of childbearing age with anemia, then becoming pregnant women with anemia, and even experiencing protein energy deficiency. The activity method is carried out by providing counseling using the Pocket Book on Anemia in the work area of ​​the Perumnas II Health Center to participants who attended as many as 30 Adolescent Girls. Community service activities have been carried out and have received a good response from adolescent girls. The pocket book distributed to participants functions as an effective tool to remind and reinforce the material that has been delivered during the counseling.